1993
DOI: 10.1590/s0036-46651993000100011
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformans var. neoformans isolado do solo

Abstract: Na tentativa de identificar a possível fonte de infecção, inquiriu-se, na história epidemiológica de 42 pacientes portadores de criptococose, o contato com pombos. Informações compatíveis com nicho ecológico do Cryptococcus neoformans foram positivas em 16. Foram colhidas 59 amostras de solo contendo fezes de pombos, penas e material orgânico. O C. neoformans foi detectado em 4. Uma das amostras era originada da capital e três do interior do estado. O sorotipo A do C. neoformans isolado de um liquor coincidiu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 6 publications
0
9
0
2
Order By: Relevance
“…Some studies carried out in Brazil reported the presence of this fungus in nests 17,31 . Although pigeons can carry C. neoformans on their beaks, feet and feathers, it remains to be showed that these ones provide appropriate nutrients for C. neoformans growth 10 .…”
Section: Discussionmentioning
confidence: 97%
“…Some studies carried out in Brazil reported the presence of this fungus in nests 17,31 . Although pigeons can carry C. neoformans on their beaks, feet and feathers, it remains to be showed that these ones provide appropriate nutrients for C. neoformans growth 10 .…”
Section: Discussionmentioning
confidence: 97%
“…Occurrence of subclinical, asymptomatic forms of the disease is unknown and studies, such as cellular immunity surveys using intradermic tests with the yeast antigen in patients without clinical disease are rare, and therefore the extent of the subclinical form has not been properly evaluated 41,48 . C. neoformans' habitat in the environment is on the ground, in decomposed vegetables, bird and bat feces which are found both in urban and rural areas of Brazil 3,5,7,27,47,50,55,58,59,66,67,75,89,90 . Studies of LAZERA et al 43,44,45,46 gave new dimensions to the ecology of the cryptococcosis agent in Brazil demonstrating that yeast is associated not only to Eucalyptus sp gender, but also to other species of trees.…”
Section: Ecological and Epidemiological Aspectsmentioning
confidence: 99%
“…MACHADO et al 27 also reported recovering this fungus from the soil in an attempt to correlate the clinical-epidemiological history of patients suffering from cryptococcosis in the Santa Casa of Porto Alegre, in the State of Rio Grande do Sul (RS), Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…However, when considering studies that examined samples of pigeon excreta, positivity rates for the isolation of the fungus in Brazil ranged from 4.3 to 31.3% 3 6 9 13 16 23 27 28 29 31 34 37 39 . The findings of this study show a positivity rate of 12% for C. neoformans , values that are compatible with the rates of isolation in Brazil previously reported in the literature.…”
Section: Discussionmentioning
confidence: 99%